2020
DOI: 10.3390/pharmacy8020099
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Michigan Female College Students about Pharmacists Prescribing Birth Control in a Community Pharmacy

Abstract: In the United States, the overall unintended pregnancy rate is about 45%. Women between 20–24 years old account for 59% of the unintended pregnancies. Continuous birth control use is related to decreasing unintended pregnancies. Therefore, we assessed female college students’ opinions about pharmacists prescribing birth control in a community pharmacy using an intersectionality framework. A survey with 49 items about provider attributes, pharmacy services use and evaluation, advantages and barriers of pharmaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Pre-pandemic studies showed that women would likely use pharmacist-prescribed BC if it was available. A study of Michigan female college students’ opinions on pharmacist-prescribed BC showed high likelihood of using this service with 46.3% reporting extremely likely and 26.3% moderately likely [ 30 ]. This study showed slightly higher likelihood to use pharmacist-prescribed BC services compared to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-pandemic studies showed that women would likely use pharmacist-prescribed BC if it was available. A study of Michigan female college students’ opinions on pharmacist-prescribed BC showed high likelihood of using this service with 46.3% reporting extremely likely and 26.3% moderately likely [ 30 ]. This study showed slightly higher likelihood to use pharmacist-prescribed BC services compared to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist-prescribed BC could increase contraception access to diverse patient populations, improve adherence, reduce unintended pregnancies, and decrease health costs [ 24 , 25 , 26 ]. In recent studies, women were highly satisfied with pharmacist-prescribed BC, benefited from the convenience of extended pharmacy hours, believed it would reduce unintended pregnancies, and expressed interest in continuing to use pharmacist-prescribed BC [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…31,32 So too are formal evaluations of patient involvement, 18 and the health outcomes associated with this service. 45 Future research comparing states' policies and reimbursement procedures for services that pharmacists offer and bill for as providers is needed to support contraceptive pharmacist-prescribing in Minnesota. Moreover, potential future research comparing outcomes of pharmacist-prescribed contraceptives between states that do and not reimburse pharmacists may provide data to support expanded reimbursement for this service.…”
Section: Implications Of the Policymentioning
confidence: 99%
“…Pharmacist services specifically targeting sexual health can also empower students to utilize health resources while on campus. One study assessing female college students' opinions about pharmacist‐prescribed hormonal contraception in a community pharmacy found “46% of students were extremely likely and 26% moderately likely to get birth control from a pharmacist,” as it would offer convenience, prevent unintended pregnancies, and be more efficient than a clinic visit 40 . Though more research is needed, there is an opportunity for pharmacists to have a positive influence on contraceptive practices, especially through education and access, among college students.…”
Section: Recommended Areas Of Focus For Expanded Pharmacist Care Services Based On Existing Literaturementioning
confidence: 99%